Use the factor theorem to determine whether g (x) is a factor of p (x) in each of the following cases.
P(x) = x^3 - 4x^3 + x + 6, g(x) = x-3
Answers
Answered by
12
Step-by-step explanation:
if p(x)= x³-4x²+x+6
x-3=0
x=0+3
x=3
p(3)= (3)³-4(3)²+ 3+6
= 27-4*9+9
= 27-36+9
= 36-36
= 0
∴ (x-3) is a factor of p(x).
Answered by
0
Answer:
kk did u get the answer ..
Attachments:
![](https://hi-static.z-dn.net/files/de0/5c8e7138f596a0eaf17016b81cf663a7.jpg)
![](https://hi-static.z-dn.net/files/d38/22e34425f71e38030203fea5eb4cc004.jpg)
Similar questions
English,
6 months ago
English,
6 months ago
Social Sciences,
6 months ago
English,
1 year ago
Biology,
1 year ago
Social Sciences,
1 year ago
Math,
1 year ago